Smart bolt for digital bolted joint monitoring system - Mohd Hafizi, Zohari; Nur Ainaa Adhreena, Muhamad Shukri; Epin, Vorathin; Mohd Padzly, Radzi (2021)
Bolted joints are critical for the safe operation in pipeline system. Previous embedded strain gauge smart bolt had been served well for a long time. However, strain gauge has disadvantages of massive cabling, prone to electromagnetic interference and harsh condition especially underwater application. Therefore, an embedded fiber Bragg grating\(FBG) smart bolt has been proposed.